Recent advances in chirality sensing/recognition using supramolecular macrocycles - Chunhong Liu (Supramolecular Materials, 2025)
Chiral sensing is crucial for understanding and controlling the biological activity of chiral molecule such as carbohydrates, amino acids, and proteins. It also plays a vital role in asymmetric synthesis, drug development, and the advancement of functional materials. Supramolecular macrocycle-based chiral sensors offer unique advantages over traditional small-molecule chiral sensors. This review highlights recent advancements in chiral sensing using supramolecular macrocycles, categorizing them into two primary groups: achiral and chiral macrocycles, based on their configurational features. Furthermore, it systematically outlines the synthetic strategies for these macrocycles, emphasizing their applications in chiral recognition and sensing.